Keanekaragaman Bakteri Pada Saluran Pencernaan Eel Elver Wild - Dea Amalia; Syifa Nur Rahmah (AGROMAKNA: Jurnal Pertanian dan Peternakan, 2026)
The Indonesian shortfin eel (Anguilla bicolor) is a member of the family Anguillidae with a wide distribution across tropical and subtropical regions. Its flesh is rich in protein, vitamins, fatty acids, trace elements, and essential nutrients. One of the key factors contributing to eel health is the balance of the gut microbiota, which plays an important role in food digestion, nutrient absorption, and immune function. This study aimed to investigate the bacterial diversity in the digestive tract of wild eel elvers. Gut microbiota diversity was analyzed using 16S rRNA metagenomic sequencing through Next-Generation Sequencing (NGS) technology. Digestive tract samples, extending from the esophagus to the anus, with a total weight of approximately 100 mg (0.1 g), were collected from 50 wild elver-stage eels obtained from Giri Mekar Village. The bacterial diversity data were analyzed using the Shannon–Wiener Diversity Index. The results showed that the gut microbiota of wild eel elvers was predominantly composed of the phyla Proteobacteria, Firmicutes, and Bacteroidetes. The dominant bacterial classes were Clostridia and Bacteroidia. The most abundant genera included Lactobacillus, Pseudomonas, Arenimonas, Parasutterella, Proteus, Aeromonas, and several unclassified bacterial taxa.